Strict Limits on Potential Secondary Atmospheres on the Temperate Rocky Exo-Earth TRAPPIST-1 d - Caroline Piaulet-Ghorayeb; Björn Benneke; Martin Turbet; Keavin Moore; Pierre-Alexis Roy; Olivia Lim; René Doyon; Thomas J. Fauchez; Loïc Albert; Michael Radica; Louis-Philippe Coulombe; David Lafrenière; et al. (The Astrophysical Journal)
The nearby TRAPPIST-1 system, with its seven small rocky planets orbiting a late-type M8 star, offers an unprecedented opportunity to search for secondary atmospheres on temperate terrestrial worlds. In particular, the 0.8 R _⊕ TRAPPIST-1 d lies at the edge of the habitable zone ( T _eq,A=0.3  = 262 K). Here we present the first 0.6–5.2 μ m NIRSpec/PRISM transmission spectrum of TRAPPIST-1 d from two transits with JWST. We find that stellar contamination from unocculted bright heterogeneities introduces 500–1000 ppm visit-dependent slopes, consistent with constraints from the out-of-transit stellar spectrum. Once corrected, the transmission spectrum is flat within ±100–150 ppm, showing no evidence for a haze-like slope or molecular absorption despite NIRSpec/PRISM’s sensitivity to CH _4 , H _2 O, CO, SO _2 , and CO _2 . Our observations exclude clear, hydrogen-dominated atmospheres with high confidence (>3 σ ). We leverage our constraints on even trace amounts of CH _4 , H _2 O, and CO _2 to further reject high mean molecular weight compositions analogous to a haze-free Titan, a cloud-free Venus, early Mars, and both Archean Earth and a cloud-free modern Earth scenario (>95% confidence). If TRAPPIST-1 d retains an atmosphere, it is likely extremely thin or contains high-altitude aerosols, with water cloud formation at the terminator predicted by 3D global climate models. Alternatively, if TRAPPIST-1 d is airless, our evolutionary models indicate that TRAPPIST-1 b, c, and d must have formed with ≲4 Earth oceans of water, though this would not preclude atmospheres on the cooler habitable-zone planets TRAPPIST-1 e, f, and g.